2017
DOI: 10.1080/02701367.2017.1376032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teaching Races for Understanding in Youth Sailing on Performance, Knowledge, and Adherence

Abstract: Teaching races for understanding can be used in sailing to improve students' capacity to reflect and connect theoretical knowledge with their motor performance in the race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 26 publications
1
35
0
6
Order By: Relevance
“…Of these, 180 were distributed in the technical group (TEG) and 177 were allocated the tactical group Table 1 shows the risk of bias of the six selected articles according to the PEDro scale. Scores varied from six to seven [22,27,28] and to eight [23][24][25]29]. Regarding the quality of evidence, the GRADE guidelines have been followed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 180 were distributed in the technical group (TEG) and 177 were allocated the tactical group Table 1 shows the risk of bias of the six selected articles according to the PEDro scale. Scores varied from six to seven [22,27,28] and to eight [23][24][25]29]. Regarding the quality of evidence, the GRADE guidelines have been followed.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Figure 2, the meta-analysis results showed that tactical intervention resulted in improvement compared with the comparison groups in almost every article (see Figure 2) and was significant in five studies [22][23][24]27,29]. However, the study by Nathan [25] reported no significant difference between TEG and TAG models in terms of skill execution or decision making.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations